Instilling the Values of Sholeh Darat Character Education - Muhammad Habib Zainul Huda; Maragustam Siregar (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
Character education values ​​are currently very much needed by students. The goal is none other than to be able to imitate the success of the previous Sholeh people. Therefore, this study will analyze the Character Education Values ​​taught by Sholeh Darat. The primary reference in this article is the Book of Faidhur Rahman by Sholeh Darat, and is also assisted by various scientific works that are in accordance with the theme. This type of research is Library Research with a Descriptive Analysis Character Study approach. The theory that the author uses is Julia Kristeva's Intertextuality. The purpose of this study is to understand the thoughts of a figure and what is applied from those thoughts. The results of this study are:1).The Characteristics of Sholeh Darat's Thoughts are Nationalist and Traditionalist Islamic. 2). The values ​​of character education instilled by Sholeh Darat are: Innovative, Multitalented, Optimistic, Humble, Honest, Compassionate, and Solidarity.